Anthropocene Childhoods Speculative Fiction, Racialization, and Climate Crisis - Ashton, Emily (Bloomsbury Academic, 2022)
Brings together the disciplines of childhood studies, literary studies, and the environmental humanities to focus on the figure of the child as it appears in popular culture and theory.